ETHNOBIOLOGICAL STUDY OF THE MANAFO TRADITION OF THE NIAS TRIBE AS LEARNING VLOG CONTENT TO SUPPORT KNOWLEDGE ON BIODIVERSITY VALUE - Adinugraha, Fajar; Gulo, Joice Elma Miranda; Halawa, Windy Setiawati; Aruan, Destri Natalia; Nitte, Tri Maharani Permata (Universitas Nias Raya, 2024)
I Indonesia is a country rich in biodiversity, but students' knowledge of the value of biodiversity is low. Efforts have been made to teach an integrated species of indigenous knowledge, Manafo. The research aims to analyze the species used in Manafo and describe the educational video about it. The research method involves field exploration with interviews and documentation techniques. The field exploration research results were used to create educational videos. The tradition of betel chewing is known as Manafo, which involves the use of five ingredients: betel leaves (tawuo), lime powder (betua), gambier (gambe), tobacco (bago), and areca nut (fino). The video was uploaded on YouTube and can be accessed through the link https://youtu.be/jyqUbjH5IZk. Respondents gave a positive and good response to the Manafo educational video. These videos are intended to support the knowledge of the younger generation while promoting cultural appreciation.